Pengaruh Gaya Belajar Terhadap Intensitas dan Prestasi Belajar Peserta Didik Di MI Al Hidayah 02 Betak Kecamatan Kalidawir Kabupaten Tulungagung - Rifqi Nuril Janah; Muhamad Zaini (Gerasi Insan Nusantara, 2024)
This research is motivated by the characteristics of students' learning methods or attitudes, known as learning styles. One of the well-known learning style theories is the